2018
DOI: 10.3389/fpls.2018.00485
|View full text |Cite
|
Sign up to set email alerts
|

Metabolome Integrated Analysis of High-Temperature Response in Pinus radiata

Abstract: The integrative omics approach is crucial to identify the molecular mechanisms underlying high-temperature response in non-model species. Based on future scenarios of heat increase, Pinus radiata plants were exposed to a temperature of 40°C for a period of 5 days, including recovered plants (30 days after last exposure to 40°C) in the analysis. The analysis of the metabolome using complementary mass spectrometry techniques (GC-MS and LC-Orbitrap-MS) allowed the reliable quantification of 2,287 metabolites. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(30 citation statements)
references
References 89 publications
3
24
0
1
Order By: Relevance
“…In addition to the direct economic benefits provided by tree species, i.e., timber and non-timber products, gaming and tourism, forests have an immensurable ecological value, being the major determinants for water, oxygen, carbon, and energy balance and can be seen as a major opportunity to mitigate climate change effects [12], i.e., continued drought, increased soil and water salinization and acidification, and intensification of extreme temperatures [13]. In forest tree metabolomics research, most biological questions are indeed related to the responses towards the acclimation and adaptation to a permanently changing environment [14][15][16][17][18][19][20][21][22][23][24][25][26] as well as to the identification of potentially active components in tree species of pharmacological, agricultural, environmental, or industrial importance [27][28][29][30][31][32][33].…”
Section: Biological Question Formulationmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition to the direct economic benefits provided by tree species, i.e., timber and non-timber products, gaming and tourism, forests have an immensurable ecological value, being the major determinants for water, oxygen, carbon, and energy balance and can be seen as a major opportunity to mitigate climate change effects [12], i.e., continued drought, increased soil and water salinization and acidification, and intensification of extreme temperatures [13]. In forest tree metabolomics research, most biological questions are indeed related to the responses towards the acclimation and adaptation to a permanently changing environment [14][15][16][17][18][19][20][21][22][23][24][25][26] as well as to the identification of potentially active components in tree species of pharmacological, agricultural, environmental, or industrial importance [27][28][29][30][31][32][33].…”
Section: Biological Question Formulationmentioning
confidence: 99%
“…In forest tree research, LC-MS instruments have also been used for untargeted secondary metabolite profiling and phytohormone quantification studies. The focus of these studies was related with abiotic stress responses [19][20][21][22][23][24]67,88,89]; and to a smaller extent to biotic stress responses [90,91] and plant growth and developmental processes [77,92,93].…”
Section: Lc-ms Metabolite Profilingmentioning
confidence: 99%
See 1 more Smart Citation
“…Las HSP fueron identificadas en condiciones de estrés por calor, pero actualmente se sabe que participan en la respuesta al estrés biótico (Yu et al, 2016), así como al frío, deshidratación, luz UV, salinidad, metales pesados, y daño mecánico (Swindell et al, 2007). Además de las HSP, hay otros grupos de compuestos que intervienen en la respuesta al choque térmico de origen muy diverso, como las citocininas, ácidos grasos, terpenoides y flavonoides que son las rutas metabólicas de mayor influencia en la respuesta a las temperaturas elevadas en Pinus radiata (Escandón et al, 2018); así como giberelinas, etileno y brasinosteroides (Clarke et al, 2009;Zhang y Wang, 2011;Dubois et al, 2018).…”
Section: Estrés Térmico (Temperatura Elevada)unclassified
“…Layer chicks also showed decreased body weight gain under increased temperatures, which is detrimental for poultry health (Tomonaga et al 2018). A study in Pinus radiata plants found crucial metabolites which can reschedule the metabolic strategy to adapt to high temperature (Escandón et al 2018). Assessing avian metabolomics under different temperatures and even food regimes could therefore provide novel insights into biochemical pathways underlying timing of breeding (in response to climate change).…”
Section: Metabolomementioning
confidence: 99%